PEMBUATAN LAMPU LED CELUP UNTUK PERIKANAN BUBU DI PERAIRAN LHOK BUBON KABUPATEN ACEH BARAT - Taufiq Taufiq; Muhammad Agam Thahir (JURNAL PERIKANAN TROPIS, 2019)
The activity of exploiting the potential of capture fisheries in the waters of West Aceh still depends a lot on the simple fishing technology. Common types of fishing gear used in West Aceh are beach seines, fishing rods, gill nets and traps. One of the success factors for fishing with traps is bait. Many previous researchers have examined traps regarding the different types of bait used. Therefore, the researcher has an idea about trap arresting devices, making renewable innovations by utilizing the light placed in the traps to lure fish to gather and enter the trap. Light is a tool to collect fish into catchable areas. The type of lamp used in this study is underwater lamps. This LED lamp is a type of lamp that is durable, energy efficient, environmentally friendly, efficient and inexpensive. The purpose of this study is to get a construction and determine the effectiveness of underwater lamps that are designed and get more catches. The research method used in this activity is a tool design method. This research was initiated by designing, making and testing tools in the laboratory and field. Data collection was carried out using descriptive methods and statistical analysis. The type of data needed in this study are primary data and secondary data. Primary data is collected by making direct measurements with related parameters such as measurements of light illumination, bubu construction, operational costs, fishing time and the type and composition of fish catches. Whereas secondary data collection by means of literature study. Data analysis used is descriptive method using data tabulation and graphical methods based on the results obtained.